2013
DOI: 10.1093/jrr/rrt103
|View full text |Cite
|
Sign up to set email alerts
|

Developing an adaptive radiation therapy strategy for nasopharyngeal carcinoma

Abstract: Adaptive radiotherapy (ART) has recently been introduced to restore the planned dose distribution by accounting for the anatomic changes during treatment. By quantifying the anatomic changes in nasopharyngeal carcinoma (NPC) patients, this study aimed to establish an ART strategy for NPC cases. A total of 30 NPC patients treated with helical tomotherapy were recruited. In the pretreatment megavoltage CT images, the anatomic changes of the posterolateral wall of nasopharynx (P-NP), neck region and parotid gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…While different numbers of replannings aimed at sparing the PG have been investigated in the literature, the optimal timing of these replannings has not been thoroughly assessed [8,13,15,16,[25][26][27][28][29][30][31][32][33][34]. The endpoint of these studies was the quantification of the dosimetric benefit of sparing the PG, while keeping or even increasing the minimum dose in the PTV, using different CT-based IMRT replanning scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While different numbers of replannings aimed at sparing the PG have been investigated in the literature, the optimal timing of these replannings has not been thoroughly assessed [8,13,15,16,[25][26][27][28][29][30][31][32][33][34]. The endpoint of these studies was the quantification of the dosimetric benefit of sparing the PG, while keeping or even increasing the minimum dose in the PTV, using different CT-based IMRT replanning scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Different ART scenarios have been investigated and compared to a classical non-ART scenario with varying numbers and timings tested: one replanning performed either mid treatment [13], at week 2 [14] or at a patient-specific time based on weight loss or tumor shrinkage [10], two replannings at weeks 2 and 4 [13,15], three replannings at the 9th, 19th, and 29th fractions [16], and, the most extensive ART strategy, six weekly replannings [8,13]. All these studies show that ART results in a decrease in the PG mean dose.…”
Section: Introductionmentioning
confidence: 99%
“…If this happens, the gland may enter into the high‐dose zone that is designed to cover the planning target volume (PTV). As a result, the parotid gland will receive a much higher than the planned dose . Since the parotid gland accounts for 60–65% of total saliva production, high dose to this organ can further increase the risk of xerostomia .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the parotid gland will receive a much higher than the planned dose. 12,13 Since the parotid gland accounts for 60-65% of total saliva production, high dose to this organ can further increase the risk of xerostomia. 14 In order to solve this problem, adaptive radiotherapy has been suggested in which the treatment plan is modified based on the tumour response and anatomical changes of OARs during a radiotherapy course.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of replanning is a controversial topic in parotid protection-based ART in head and neck cancer. Someone recommended replanning when it became obvious that a tumor had shrunk, weight loss had occurred, or skin separation had reduced [7,11,12,[21][22][23], while others believe that replanning should be performed when a specific fraction has been reached [26][27][28]. Our precious study found that parotid volume variation presented a linear pattern throughout IMRT of NPC realized by HT technique, and the rate of volume variation reached its peak at the 16th fraction and then decreased gradually, suggesting that replanning is appropriate in the fourth week [14].…”
Section: Discussionmentioning
confidence: 99%